RISK ANALYSIS FOR SHIP CONVERTING PROJECT ACCOMPLISHMENT (Case study of KRI KP Converting Project) - Endro W, Dimas; Wiediartini, Wiediartini; Iviana J, Anda (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2013)
Ship converting has become as prospective activity in ship building area. Operational and economical aspect are the most dominant rationale. Baseon a new fuction of converted ship, a task list which contain several jobs that must be done is listed. This accomplishment schedule not only contain a task list, but also duration for certain job title. In practical apllication job duration is maintained based on experience of project manager.Â  Further more, total accomplish duration is setted as time accomplishment for the project. This setted time has become reference for the project bid. Occasionaly, if accomplishment time which offered is strict, than schedule slip become as potencial nightmare. For this situation, project manager has had a cristal clearconsideration to select a proper decision wheter he will take the tender offer or not. practically, project mananger has layed on his experience to handle previous project and faceÂ  penalty if the project delayed. This paper focussed on how to measure tender offer based on risk analysis, specially for converted ship tender which has a strike time accomplishment.A new application method to analysis proposed tender based on time and penalty parameter has become a topic of this paper.